2015
DOI: 10.1007/s10509-014-2136-z
|View full text |Cite
|
Sign up to set email alerts
|

UV spectral diagnostics for low redshift quasars: estimating physical conditions and radius of the broad line region

Abstract: The UV spectral range (1100 -3000Å) contains the strongest resonance lines observed in active galactic nuclei (AGN). Analysis of UV line intensity ratios and profile shapes in quasar spectra provide diagnostics of physical and dynamical conditions in the broad line emitting region. This paper discusses properties of UV lines in type-1 AGN spectra, and how they lead an estimate of ionizing photon flux, chemical abundances, radius of the broad line emitting region and central black hole mass. These estimates are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Many studies have suggested that the broad emission-line flux ratios of quasars at the rest-frame ultraviolet and optical wavelength can provide accurate chemical abundance measurements in quasar BLRs (Hamann et al 2002;Warner et al 2003;Dietrich et al 2003;Nagao et al 2006;Matsuoka et al 2011;Marziani et al 2015;Sameshima et al 2017). The theoretical accuracy of any broad emission-line flux ratios as metallicity indicators depends on a variety of factors such as the central radiation field, temperature sensitivity of the emission-line ratio, the similarity of the ionization potentials and critical densities, the extent to which the line-emitting regions overlap spatially (Hamann et al 2002).…”
Section: Metallicity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have suggested that the broad emission-line flux ratios of quasars at the rest-frame ultraviolet and optical wavelength can provide accurate chemical abundance measurements in quasar BLRs (Hamann et al 2002;Warner et al 2003;Dietrich et al 2003;Nagao et al 2006;Matsuoka et al 2011;Marziani et al 2015;Sameshima et al 2017). The theoretical accuracy of any broad emission-line flux ratios as metallicity indicators depends on a variety of factors such as the central radiation field, temperature sensitivity of the emission-line ratio, the similarity of the ionization potentials and critical densities, the extent to which the line-emitting regions overlap spatially (Hamann et al 2002).…”
Section: Metallicity Measurementsmentioning
confidence: 99%
“…The BLRs contain gas clouds close to the SMBHs, which are photoionized by the radiation field from the accretion disk of the SMBH. The ultraviolet and optical emission lines from BLRs are widely ⋆ E-mail: astroxf@163.com † E-mail: fbian@eso.org used to estimate the SMBH mass (Vestergaard & Peterson 2006;Shen 2013;Zuo et al 2015) and the chemical abundance close to the SMBH (Hamann et al 2002;Nagao et al 2006;Jiang et al 2007;Juarez et al 2009;Matsuoka et al 2011;Marziani et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The issue of the intensity ratios of the doublet components is relevant to the spectral analysis of high-z quasars or low-z type-1 AGNs observed from spaceborne observatories [51]. As the lines originate from the transition between the same spectroscopic terms, we would expect that, in the case of optically thin line emission, the ratio is equal to the ratio of the statistical weight of each level, i.e., g j /g i = (2J j + 1)/(2J i + 1), implying a maximum ratio of two for the ratio between the J = 3 2 and the J = 1 2 components of the doublet, I( 2 P o 3 2…”
Section: Applications To Empirical Line Profile Modeling: Intensity Rmentioning
confidence: 99%
“…The subsquent tasks will be to check the R FeII dependence on other parameters (see Sulentic et al, 2000;Mao et al, 2009;Marziani et al, 2015) which are used (L bol , α uv , α ox , n H , N H , cos(i), a and others). We intend to incorporate the microturbulence as suggested in Bruhweiler and Verner (2008).…”
Section: Futurementioning
confidence: 99%